2018
DOI: 10.3390/molecules23020410
|View full text |Cite
|
Sign up to set email alerts
|

Ent-Clerodane Diterpenes from the Bark of Croton oligandrus Pierre ex Hutch. and Assessment of Their Cytotoxicity against Human Cancer Cell Lines

Abstract: New clerodane diterpenes, 12-epi-megalocarpodolide D (2) and an epimeric mixture of crotonolins A (3) and B (4), were isolated from the bark of Croton oligandrus following a bioassay-guided isolation protocol. Known compounds, megalocarpodolide D (1), 12-epi-crotocorylifuran (5), cluytyl-ferulate (6), hexacosanoyl- ferulate (7), vanillin (8), acetyl-aleuritolic acid (9) and lupeol (10), were also isolated. The structures of the isolated compounds (1–10) were elucidated by spectroscopic means. The cytotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
4
7
0
1
Order By: Relevance
“…Their FTIR spectrum showed absorption bands of hydroxy (3465 cm -1 ), ɤ-lactone (1775 cm -1 ), α, β-unsaturated lactone (1712 cm -1 ) and olefinic (1670 cm -1 ) groups. Their 1 H and 13 C NMR data rather similar to those of clerodanes crotonolins A and B (1-2), previously isolated from the same plant (Guetchueng et al, 2018) suggested that these compounds were structurally close. Complete assignment of rings A and B and their respective substituents could be achieved easily by comparison of the observed chemical shifts of 3 and 4 with those of crotonolins A and B (1-2).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Their FTIR spectrum showed absorption bands of hydroxy (3465 cm -1 ), ɤ-lactone (1775 cm -1 ), α, β-unsaturated lactone (1712 cm -1 ) and olefinic (1670 cm -1 ) groups. Their 1 H and 13 C NMR data rather similar to those of clerodanes crotonolins A and B (1-2), previously isolated from the same plant (Guetchueng et al, 2018) suggested that these compounds were structurally close. Complete assignment of rings A and B and their respective substituents could be achieved easily by comparison of the observed chemical shifts of 3 and 4 with those of crotonolins A and B (1-2).…”
Section: Resultssupporting
confidence: 64%
“…Reversed-phase HPLC separation of the methanolic extract of C. oligandrus yielded, in addition to the previously reported compounds (Guetchueng et al, 2018), four new neoclerodanes, named crotonolins C-F (3-6) along with the known clerodane crotonzambefuran A (7) (Ngadjui et al, 2002), the abietanes 7-β-hydroxydehydroabietic acid (8) and 7oxodehydroabietic acid (9) (Tanaka et al, 1997) and ferulic acid (10) (Nguyen et al, 2004) ( Figure 1). The known compounds (7-10) were identified by comparison of their spectroscopic data with their corresponding available data in the literature.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…sylvaticus [ 12 ] and the roots of C. limae [ 13 ], respectively. Eight new clerodane diterpenoids with butenolide at C-9 ( 2 , 3 , 5 , 13 , 14 , 75 , 91 , 92 ) were obtained from three Croton species ( C. crassifolius , C. glabellus , and C. oligandrus ) [ 14 , 15 , 16 , 17 , 18 ]. Furan-clerodane diterpenoids are abundant in Croton species, and 82 new ones were isolated from different Croton species.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…properties (Agbor et al, 2014). As a part of our continuing study on the secondary metabolites of Cameroonian medicinal plants (Wansi et al, 2016;Guetchueng et al, 2017Guetchueng et al, , 2018aGuetchueng et al, , 2018b, we have undertaken the phytochemical investigation of Ruspolia hypocrateriformis. The present work describes the isolation and identification of two new flavone glycosides (1 and 2) from the leaves of this plant (Figure 1).…”
Section: Introductionmentioning
confidence: 99%